Outcomes of Interventions for Angiosarcoma - Yan, Qi; Fernandez, Roman A.; Elmi, Maryam; Gelfond, Jonathan; Davies, Mark G. (Frontiers in Surgery, 2022)
Objective: The management and outcome of angiosarcoma, a rare malignant vascular tumor, is not well described. The aim of this study is to report the incidence, patient demographic, and outcomes based on national data. Methods: Data on patients with angiosarcoma were obtained from Surveillance, Epidemiology, and End Results (SEER) database. Inverse probability treatment weights were used to assess survival benefit of surgery versus no surgery in patients initially offered surgery and survival benefit of surgery plus chemo or radiation therapy compared to surgery alone. Cox regression was used to assess survival. Statistical analysis was performed on RStudio. Results: 5135 patients (46%, male; median age 69yrs) with angiosarcoma were identified in SEER database between 1975-2006. Age adjusted incidence rate was 0.1%-0.4%. Average tumor size was 4.7, range (0.1-98.9) cm. Tumor grades was high at presentation (Grade III 17.2%, Grade IV 19%, unknown 50.6%) however, half were considered localized tumors. Most patients underwent surgery alone (37.3%); The remainder underwent combination therapy of surgery with radiation therapy (13.3%), surgery with chemotherapy (9.8%) and all three treatments (6%). In 5.6% patients, surgery was recommended but not performed. Median overall survival was 13 months (range, 0-483 months) and overall 5-year survival was 26.7% (95% CI 25.4-28.1%). A total of 2561 patients met criteria for survival analysis, Male gender, older age, higher tumor grade, advanced stage, tumor without laterality, primary site of visceral, larger tumor size were independent predictors of poor outcome in multivariate analysis. Head and neck primary site and any single or combination of treatment, except for radiation therapy only, were independent predictors of improved outcome. Decade when angiosarcoma was diagnosed, SES index, race and ethnicity were not predictive of mortality. Inverse probability treatment weights adjusted Cox proportional hazard model demonstrated worse survival show that surgery compared to no surgery and sugery with chemo/radiation compared to surgery alone has worse survival between month 0-25 but improved survival after month 25. Conclusions: The incidence of angiosarcoma is low and long-term survival is poor. Multimodal therapy in the forma of neoadjuvant or adjuvant chemo/radiation therapy offer significant long-term survival benefits over surgery alone.